1976
DOI: 10.1007/bf00239784
|View full text |Cite
|
Sign up to set email alerts
|

Etude ultrastructurale quantitative du pericaryon de la cellule de Purkinje et de son environnement chez le rat normal et hypothyro�dien ag�s de 21 jours

Abstract: The effects of neonatal hypothyroidism on synaptic organization, glial surrounding and cytoplasmic structures of the Purkinje cell perikaryon of the 21 days old rat were studied by electron microscopy. Hypothyroidism decreases the size of the perikaryon but does not change the nucleo-cytoplasmic ratio of the cell. At 21 days the axonal endings that make synapse on the Purkinje cell perikaryon, already show the adult morphological features and hypothyroidism does not change these. The general synaptic density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The sudden drop in cerebellar weight was not attributed to the higher than normal cerebellar bilirubin levels, but instead appeared to correlate with the decrease in cerebellar thymidine kinase activity (14,27) which occurs as early as 6 days postnatally. It is noteworthy that Dainat and Rebi6re (28) found precursor incorporation into RNA and DNA of the cerebellum of the Wistar rat to be maximal at 6 and close to minimal at 21 days, a time when cerebellar development also nears completion (13,29) and when homologous cerebellar tRNA methylation (examined in the Sprague-Dawley rat) is significantly different from its 6 day levels (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…The sudden drop in cerebellar weight was not attributed to the higher than normal cerebellar bilirubin levels, but instead appeared to correlate with the decrease in cerebellar thymidine kinase activity (14,27) which occurs as early as 6 days postnatally. It is noteworthy that Dainat and Rebi6re (28) found precursor incorporation into RNA and DNA of the cerebellum of the Wistar rat to be maximal at 6 and close to minimal at 21 days, a time when cerebellar development also nears completion (13,29) and when homologous cerebellar tRNA methylation (examined in the Sprague-Dawley rat) is significantly different from its 6 day levels (8,9).…”
Section: Discussionmentioning
confidence: 99%
“…Although early studies suggested that pro pylthiouracil may have a neurotoxic effect in adult brain [56], recent examination of pro pylthiouracil-induced neonatal hypothyroi dism has shown that most effects are reversed by concurrent thyroid hormone treatment [8,29,39],…”
Section: Discussionmentioning
confidence: 99%
“…In hypothyroid young rats, administration of 0.5 or 1.0 pg/day of thyroxine for a week, before the 28th postnatal day, partially adjusted the abnormalities in synaptogenesis of the molecular layer (Rebikre & Dainat 1976a). On the other hand, administration of 2 or 4 ,&day of thyroxine for a week before the 14th postnatal day, restored Purkinje cells development and the rate of disappearance of the cerebellar granular layer (Legrand 1967b).…”
mentioning
confidence: 99%